The Role of Managerial Skills Through Coaching Within the Contemporary Economy - Ionela STANCA PETRUTA; Denisa Mihaela ȘULĂ; Liliana NICOLAE ȘTEFAN (Revista de Management Comparat International, 2023)
The research aims to study the improvement of managerial skills through coaching, in service-providing and goods-producing industries. The reason for this research started from the need for studies on the coaching market in Romania that would result in concrete data regarding the level of benefits that such services can provide to clients from various industries. The need is to be able, both as a provider and as a user of coaching services, to refer to certain values that determine whether coaching services bring added value, and if so, how much. Starting from this need and from the theoretical areas of known benefits that coaching services bring to clients, the area on which the research will be focused was determined. Thus, the main objective was defined as obtaining a package of values that would determine the level of impact of coaching services on the managerial skills of management personnel in Romanian industries. This general objective gave birth to the objective of determining a model of managerial skills with an impact on managerial performance, which can be developed and improved through coaching programs.